2009
DOI: 10.4049/jimmunol.0802528
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Evolution of IFNs: Zebrafish Group II IFNs Induce a Rapid and Transient Expression of IFN-Dependent Genes and Display Powerful Antiviral Activities

Abstract: The IFNs and their receptors have existed in early chordates for ∼500 million years and represent the early elements in innate and adaptive immunity. Both types I and II IFNs have been discovered in fish, and type I has recently been classified into two groups based on their primary protein sequences. However, the biological activities of fish IFNs and their roles in infection are largely unknown. Using the zebrafish and manageable bacterial (Streptococcus iniae) and viral (spring viremia of carp virus) infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
99
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(109 citation statements)
references
References 21 publications
4
99
2
4
Order By: Relevance
“…Recently virus-induced IFN genes have been cloned in some teleost fish and their antiviral activities have been proved in vitro and in vivo (Altmann et al, 2003;Long et al, 2004;Lopez-Munoz et al, 2009;Lutfalla et al, 2003;Ooi et al, 2008;Robertsen et al, 2003;Zou et al, 2007). In the present study, using gain-of-and loss-of-function experiments, we demonstrated that fish IFN confers a strong resistance to virus infection through induction of a set of conserved ISGs and, importantly, IFN upregulates ISGs and itself through Stat1 pathway.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Recently virus-induced IFN genes have been cloned in some teleost fish and their antiviral activities have been proved in vitro and in vivo (Altmann et al, 2003;Long et al, 2004;Lopez-Munoz et al, 2009;Lutfalla et al, 2003;Ooi et al, 2008;Robertsen et al, 2003;Zou et al, 2007). In the present study, using gain-of-and loss-of-function experiments, we demonstrated that fish IFN confers a strong resistance to virus infection through induction of a set of conserved ISGs and, importantly, IFN upregulates ISGs and itself through Stat1 pathway.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, some authors suggest a new name, IFN s, for fish virus-induced IFN (Stein et al, 2007). However, it is obvious that fish virus-induced IFNs are classified into two groups , which display powerful and complementary antiviral activities (Lopez-Munoz et al, 2009). The discrepancy between the two groups has been verified further by analysis of receptor usage (Aggad et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We next evaluated the disease resistance of CONR and GF zebrafish larvae at 72 hpf using a spring viremia of carp virus (SVCV) infection model (43) in which the virus is cleared by the IFN system (43,44). Interestingly, the naturally primed CONR group showed increased resistance to SVCV as compared with GF larvae (Fig.…”
Section: Microbial Priming By Commensal Microbes Is Essential For Promentioning
confidence: 99%
“…In zebrafish, there are four members of type I IFNs (Aggad et al, 2009;Lopez-Munoz et al, 2009), and two members of type II IFNs, IFNc1 and IFNc2 (Igawa et al, 2006;Sieger et al, 2009). Previously we confirmed both types of zebrafish IFNs activate zebrafish IRF9 promoter in epithelioma papulosum cyprini cells (EPC) (Shi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, zebrafish Danio rerio genome has four IFNu genes (DrIFNu1/ 2/3/4, or named DrIFN1/2/3/4) most similar to mammalian type I IFN, and two IFNc genes (DrIFNc1/2) orthologous to mammalian type II IFN (Aggad et al, 2009;Lopez-Munoz et al, 2009;Sieger et al, 2009). To determine whether two types of fish IFNs could induce crucian carp viperin expression, the roles of these zebrafish IFNs in activation of crucian carp viperin promoter and induction of viperin mRNA and proteins were investigated.…”
Section: Induction Of Viperin By Two Types Of Fish Ifnsmentioning
confidence: 99%